Murder at the Lemonberry Tea - Hannah, Darci (Hannah, Darci. Beacon Bakeshop mystery., 2024)
"Lindsey's patrons have a new outdoor patio where they can eat their treats in the glorious summer weather. But even more exciting is that the Beacon Bakeshop is going to host British celebrity chef Vivi Lemonberry--and what could be a more appropriate event than a tea party? What Lindsey didn't realize is that Vivi is here to put some distance between herself and her recent professional and personal scandals. Despite assurances that Vivi is as sweet as a chocolate-dipped strawberry, Lindsey is cooling rapidly toward the culinary icon... especially after she banishes Lindsey's beloved dog, Wellington, from the bakeshop and then flirts outrageously with Lindsey's boyfriend. She's not the only one feeling hostile, though. While Vivi's in the middle of making a tart in front of the cameras, a woman runs up and slaps her. Soon, Vivi's nowhere to be found, and folks are speculating on whether she's run off with her secret lover or just laying low due to embarrassment. That is, until Lindsey finds a body bobbing near the surface of Lake Michigan. It's a sour ending for the diva, but Lindsey is determined to squeeze the truth out of every clue until she finds the killer..."--